INTEGRATION OF THE OUTPUT OF A SILICON SOLAR CELL TO THE GRID SYSTEM - Azim, Md. Imran; Rahman, Md. Rajibur; Rahman, Md. Fayzur (European Scientific Journal, ESJ, 2013)
With the advent of the 21st century, the utilization of renewable energy in modern power generation has been leapt to a level that was unimaginable only even 100 years ago. Solar energy is one of the popular renewable energy sources as it is abundant in nature especially warm predominant countries like Bangladesh. In addition, some noteworthy upsides of solar energy are free fuel such as sunlight is free, environmental friendly operation, minimal maintenance and longer service life. This paper furnishes knowledge about the performance of a single crystalline silicon solar cell, based on the practical experimental results that have been obtained from different connections of the used modules like single module, series connection of double modules and parallel connection of double modules. The comparative results show that maximum open circuit voltage, maximum output power and maximum fill factor have been obtained from series connection of double modules whereas, parallel connection of double modules has given the largest amount of short circuit current. On the other hand, highest efficiency has been derived in case of single module connection. Besides, suitable arrangements have also been demonstrated in this paper so that the output of these solar modules can be connected to the grid system with a view to meeting up the increased power demand.